Mind and Action in Fakhr Al-Din Al-Razi Philosophy - Alkhalaileh, Ayman; Altawallbeh, Mohammad (Jordan Journal of Social Sciences, 2021)
There is no doubt that Imam Fakhr Al-Din Al-Razi is considered remarkable in the history of Islamic thought, because he came at a time when the linking of Greek philosophy to the Islamic religion was ended on one hand and the beginning of the emergence of new philosophies in Islamic thought, namely the oriental philosophies on the other hand, so it is considered the end of a period and the beginning of a new period. The subject of this study deals with the mind and action, and we mean here the relationship of Divine Mind and the Divine Action with human mind and action, and we find that he Benefits from Muslim Philosophers., specifically the Imam Al-Ghazali, And his students. The methodology of this research is based on the study of Al-Razi’s thought through a logical historical approach in which we track the issues that Al-Razi dealt with and try to reconstruct it logically so that we can reach to an understanding of his point of view. The study addresses Al-Razi's definitions of concepts related to the subject such as Divine Will, Divine Knowledge, Divine Power, and Divine Action. Then the study moves on to human mind and action, so that their relationship to Divine Knowledge and Action.